Economic And Social Dynamics in the urban frontier agglomeration of Corumbá/BR, Puerto Quijarro and Puerto Suárez/BO: an analysis based on commuting (PerCursos, 2022)
This work seeks to understand the economic and social dynamics that occur in the urban frontier agglomeration composed of Corumbá/BR, Puerto Quijarro and Puerto Suárez/BO, through commuting. It is a common phenomenon in these areas that characterizes and distinguishes them. Therefore, we sought to discuss the elements of commuting, then approach the genesis and development of this agglomeration. Finally, an analysis of the pendular displacements that occur there is outlined. It was understood that it is through these displacements that a large part of the population ensures their work, in addition to the consumption of goods and services.
Keywords: Corumbá; Puerto Suárez; Puerto Quijarro; commuting; frontier